Chinese and African perspectives on China in Africa - Harneit-Sievers, Axel (Cape Town Pambazuka Press, 2010)
The deepening engagement of China in Africa since the end of the cold war has led to debates about the evolving nature of this relationship. Yet the focus of analysis has largely been confined to interactions between states. Little attention has been paid to the growing dialogue between Chinese and African civil society organisations (CSOs). This collection of essays, written by scholars and activists, explores the interaction between African and Chinese non-state actors and argues that the future of Africa-China relations rests on including such voices if a robust and vibrant engagement and meaningful relationship are to be sustained. Arising from a workshop held in Nairobi in April 2008 and co-hosted by Fahamu with the Heinrich Boll Foundation(Kenys), this is the third in series published by Pambazuka press attempting to develop an authentic Africa-China discourse among civil society organisations around social justice. Chinese and African Perspectives on China in Afirca assesses China's actvities in Africa through patterns of investment, legal cooperation, effects on the environment,trade,aid and labour links,questions of peace,security and stability, the African Union response, possible regulatory interventions and the future strengethening of an Africa-China CSO dialogue.
Includes index
Keywords: Africa-Foreign relations- China, China-Foreign relations- Africa